Survei Praktik Keuangan Usaha Mikro, Kecil dan Menengah - Lusianus Heronimus Sinyo Kelen; Muhammad Rifaldy (Strategic: Journal of Management Sciences, 2022)
Objective This study aims to conduct a survey on the financial practices of micro, small and medium enterprises in Waingapu City District, especially in the study of culinary businesses. Research Method. This research uses a quantitative descriptive method with a survey technique of 75 respondents. Results. The results of the study show that there are three things, namely the amount of capital used, sources of business capital, and financial records carried out or not in MSMEs. Conclusion. The results of this survey indicate that there are several things that can be concluded, namely: first, most of them use their own capital. Second, the survey results show that all MSMEs in Waingapu City District are included in the criteria for micro-enterprises. The three survey results show that the majority of MSME owners in Waingapu City do not keep financial records.